1995
DOI: 10.1152/ajplung.1995.269.4.l453
|View full text |Cite
|
Sign up to set email alerts
|

Cellular uptake of albumin from lungs of anesthetized rabbits

Abstract: Resolution of alveolar edema depends on clearance of serum protein, as well as liquid from the alveolar space. Protein clearance is slower than liquid clearance and may take days to weeks. Our earlier studies presented evidence for the importance of paracellular removal of soluble protein from the air spaces. However, long-term protein clearance may also depend on uptake by alveolar epithelial cells or macrophages. This study examined cellular uptake of soluble human albumin and insoluble colloidal gold-albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
1
11
1
1
Order By: Relevance
“…Alveolar macrophages are well known for their capacity to endocytose and degrade exogenous protein and peptides (74). Their endocytic capacity is greater than that of type II alveolar epithelial cells (36). However, alveolar macrophages do not appear to play a major role in clearing protein over 24-48 h from the alveoli of the normal lung.…”
Section: Alveolar Degradationmentioning
confidence: 99%
“…Alveolar macrophages are well known for their capacity to endocytose and degrade exogenous protein and peptides (74). Their endocytic capacity is greater than that of type II alveolar epithelial cells (36). However, alveolar macrophages do not appear to play a major role in clearing protein over 24-48 h from the alveoli of the normal lung.…”
Section: Alveolar Degradationmentioning
confidence: 99%
“…However, as the supernatant and tissue were analysed in our model it suggests that carbonylated HSA could be degraded by the parenchymal lung explants. In support of this finding, it has been demonstrated that both albumin and other high molecular weight proteins can be directly cleared by the epithelium through epithelial receptor mediated endocytosis or pinocytosis, and these proteins are catabolised through lysosomal degradation (30)(31)(32). Recent evidence suggests that oxidation of HSA decreases its denaturation enthalpy, suggesting that oxidation of HSA renders it to be denatured more easily (33).…”
Section: Discussionmentioning
confidence: 92%
“…The free fluorescent label did not localize intracellularly. The data suggest that the cellular uptake of antioxidants and other proteins delivered IT may occur via a nonspecific mechanism [21,22]. This may explain how the rhSOD is taken up by cells in the lung and why the half-life of the protein is approximately 48 h. These observations have important implications for clinical trials in newborn infants.…”
Section: Rhsod Localization Studiesmentioning
confidence: 92%
“…This suggests that the pathogenesis of BPD is multifactorial and associated with a variety of causative factors. Since the lungs of critically ill premature and term infants with lung disease are exposed to supraphysiological oxygen concentrations during therapy, it seems logical that an oxidative insult could be an important component of the injury process [Saugstad, pp [21][22][23][24][25][26][27][28]. BPD has been hypothesized to begin as acute inflammatory changes secondary to toxic free oxygen radicals which then evolve into chronic lung disease [1,4,5].…”
Section: Introductionmentioning
confidence: 99%